Microstrip tapered traveling wave antenna for wide range of beam scanning in X- and Ku-bands - Gunes, Filiz; Belen, Aysu; Belen, Mehmet A. (WILEY, 2019)
In this work, a broadband traveling wave antenna (TWA) is presented as a microstrip design that is capable of a wide range of beam scanning by changing the operation frequency within 8 to 14 GHz. For this purpose, a rhombus shaped microstrip patch is used as a unit element and TWA is built as a tapered microstrip line consisting of the cascaded rhombus shaped unit elements and terminated by a rectangular antenna instead of traditional resistive termination which can be called patch loaded traveling wave antenna (PLTWA). Optimization and simulation of the PLTWA is carried out using 3-D Microwave simulation software CST and its dimensions are resulted as 130 x 30 mm. From the simulations, it should be noted that the patch termination increases the maximum gain almost 3 dB and the total efficiency up to 90% compared to the traditional resistive load over the operation band at the expanse of a small distortion on S-11 characteristics. Then the PLTWA is fabricated and measured along its operation band 8 to 14 GHz and it exhibits a peak gain of 9.5 dBi at 11 GHz. The measured gain of the proposed antenna is found between 9 dB and 12 dB and its beam direction is steerable with the range of 80 degrees (-65 degrees-15 degrees) over the operation band 8 to 14 degrees GHz.
Keywords: beam scanning; reconfigurable antenna; traveling wave antennas; RADIATION-PATTERN; ARRAY; FREQUENCY; BROADSIDE; DESIGN; Computer Science; Engineering